Novel Geobacter species and diverse methanogens contribute to enhanced methane production in media-added methanogenic reactors. (15th December 2018) - Mei, Ran; Nobu, Masaru K.; Narihiro, Takashi; Yu, Jimmy; Sathyagal, Arun; Willman, Eric; Liu, Wen-Tso
Abstract: To determine whether the addition of conductive materials could enhance methane production by direct interspecies electron transfer (DIET), we operated three anaerobic reactors amended with non-conductive (ceramic) or conductive materials (anthracite and granular activated carbon (GAC)). Throughout eight months of operation, ethanol was consistently detected as the major fermentation product. The specific yield in the anthracite and GAC-added reactors increased by 31.5% and 43.3%, respectively, compared to the ceramic-added reactor. 16S rRNA gene sequencing results indicated Geobacter was dominant (up to 55% of total sequences), whereas acids-degrading syntrophic bacteria were low in abundance (<2%). Using metagenomic analysis, the draft genome of the dominant Geobacter population (bin GAC1) was reconstructed and observed to possess genetic abilities of ethanol oxidation, hydrogen production, and extracellular electron transfer, and represented a phylogenetically novel Geobacter species. While Methanosaeta was the dominant methanogen, reactors containing conductive materials harbored more diverse and abundant archaeal populations, as revealed by FISH, qPCR, and metagenomics. Our findings suggested that a novel Geobacter population could oxidize ethanol and employed both hydrogen transfer and DIET depending on the accessibility of conductive materials. Thermodynamic advantages of DIET over hydrogen production could lead to enhanced methane production in reactors with conductive materials. Graphical abstract: Highlights: Methane production was enhanced by addition of conductive materials. A novel Geobacter species has genetic capacity of hydrogen production and DIET. Thermodynamic advantages of DIET may contribute to enhanced methane production. 16S rRNA gene, FISH and qPCR revealed diverse methanogens associated with GAC.